2013
DOI: 10.1111/aec.12001
|View full text |Cite
|
Sign up to set email alerts
|

Habitat fragmentation in forests affects relatedness and spatial genetic structure of a native rodent, Rattus lutreolus

Abstract: Habitat fragmentation can have a range of negative demographic and genetic impacts on disturbed populations. Dispersal barriers can be created, reducing gene flow and increasing population differentiation and inbreeding in isolated habitat remnants. Aggregated retention is a form of forestry that retains patches of forests as isolated island or connected edge patches, with the aim of 'lifeboating' species and processes, retaining structural features and improving connectivity. Swamp rats (Rattus lutreolus) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
(204 reference statements)
0
8
0
Order By: Relevance
“…For example, more than 75% of naturally occurring deciduous forests in eastern and midwestern North America were cleared by 1850, primarily for agriculture (Stein et al 2000). This conversion of native forests has increased habitat fragmentation (Demers et al 1995;Stephens et al 2013) and isolated populations that were historically connected genetically, thereby increasing inbreeding depression (Mills 1995;Keller and Waller 2002). Increased fragmentation has also produced more field-forest edges, increasing the negative impacts of edge effects on forest interior species (Hargis et al 1999;Gehring and Swihart 2003;Elliott and Root 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, more than 75% of naturally occurring deciduous forests in eastern and midwestern North America were cleared by 1850, primarily for agriculture (Stein et al 2000). This conversion of native forests has increased habitat fragmentation (Demers et al 1995;Stephens et al 2013) and isolated populations that were historically connected genetically, thereby increasing inbreeding depression (Mills 1995;Keller and Waller 2002). Increased fragmentation has also produced more field-forest edges, increasing the negative impacts of edge effects on forest interior species (Hargis et al 1999;Gehring and Swihart 2003;Elliott and Root 2006).…”
Section: Introductionmentioning
confidence: 99%
“…When the global genetic divergence between populations is analyzed, the wood mouse shows much weaker population structure than the bank vole. This pattern is expected considering that, at a short geographic scale (distances <30 km), genetic structure is commonly found only in rodents with a specialized ecological niche 7379 .…”
Section: Discussionmentioning
confidence: 67%
“…Frugivorous rodents fulfill a role as seed dispersers, contributing to the spatial dynamics of plants populations during a key-stage of their life cycle (Nyiramana et al, 2011;Choo et al, 2012;López-Barrera, Newton & Manson, 2005;Forget et al, 2011). At the same time, plants provide rodents with the energy needed to complete their own life cycles (Stephens et al, 2013;Johnstone, Lill & Reina, 2014). In addition to their role as dispersal agents, rodents play several other roles within trophic webs (Martínez Ramos, 2008): they are an important source of energy for bigger mammals, function as biocontrol agents (Hanski, 1987), contribute to the nutrient cycles of soil while grazing in forest ecosystems (Virtanen, 2000;Hoset et al, 2014), and, in the case of the fossorial species, modify vegetation composition and abundance, nutrients dynamics, capture of water, and soil texture ( Reichman & Seabloom, 2002;Kerley, Whitford & Kay, 2004;Arias Caballero, 2011).…”
Section: Assessing Five Species Of Cloud Forest Rodents Of Mexicomentioning
confidence: 99%
“…As a result of this process, cloud forests, as montane vegetation ecosystems in general, are becoming fragmented, sustaining only isolated vegetation patches that reduce the quality and quantity of the habitat for forest-dependent species (Lindenmayer, Cunningham & Pope 1999). Stephens et al (2013) demonstrated that even the smallest fragmentation, such as a road or walk path, can change the genetic structure of small species populations as those of rodents. Additionally, edge effect, another consequence of habitat loss and fragmentation (Lindenmayer, Cunningham & Pope, 1999), is common in landscapes next to disturbed areas.…”
Section: Assessing Five Species Of Cloud Forest Rodents Of Mexicomentioning
confidence: 99%